Impact of genotypic and phenotypic resistance to second-line anti-tuberculosis drugs on treatment outcomes in multidrug-resistant tuberculosis in China - Yi Hu; Xubin Zheng; Zhu Ning; Qun Li; Zhengdong Zhang; Sven Hoffner (International Journal of Mycobacteriology, 2016)
Background: Despite the strong association between drug resistance and genetic mutations, the value of molecular diagnosis of drug resistance to guide the treatment of multidrug-resistant tuberculosis (MDR-TB) remains unclear. This is particularly relevant in resource-limited areas, in which it is difficult to implement the drug susceptibility test. Here, we focused on the association of drug susceptibility phenotype and genotype with treatment outcomes in patients with MDR-TB. Methods: In a prospective cohort study, we enrolled 252 consecutive patients with confirmed MDR-TB between 2010 and 2013, and outcomes were followed-up over the 24-month treatment course in terms of clinical manifestation and sputum conversion. All the isolates were tested for phenotypic susceptibility to second-line drugs in the Mycobacteria Growth Indicator Tube based system, and genotypic mutations were assessed by DNA sequencing. Results: Among the 252 MDR-TB isolates, 88 (34.9%) were resistant to fluoroquinolones and/or second-line injectable drugs, of which 65 (73.9%) harbored a mutation in drug resistance-related genes (gyrA, rrs and eis). In addition, 85 individuals (33.7%) were also resistant to pyrazinamide, with 87.1% containing the pncA mutation. Of 252 MDR-TB patients, 207 (82.1%) had known outcomes and 45 (17.9%) were lost to follow-up. Among those with known outcomes, treatment succeeded in 85.8% with plain MDR-TB, 69.7% with initial resistance to either a fluoroquinolone or second-line injective drugs, 37.5% with initial resistance to pyrazinamide, 29.3% with initial extensively drug resistance. In contrast, among those with known outcomes, treatment success and culture conversion depends on the susceptibility to drug especially for pyrazinamide and fluoroquinolones. In multivariate analysis, pyrazinamide resistance and its related pncA gene mutation were independently associated with a lower risk of culture conversion on at 8 weeks and treatment success, while fluoroquinolone resistance was negatively correlated with treatment success. Besides, specific treatment, patient and program variables were also associated with treatment outcome. Conclusion: Drug susceptibility testing for pyrazinamide and fluoroquinolones together with genetic information appears to provide a clinically useful indicator of the treatment outcome of MDR-TB in China.